PENERAPAN MARKETING MIX SEBAGAI STRATEGI PEMASARAN JASA PENDIDIKAN DI MTS NEGERI CILACAP - Miftah Khoeriyah; Siti Baro'ah; Anis Afiqi, Muhammad (Jurnal Tawadhu, 2023)
This research aims to determine the application of marketing mix as a marketing strategy for educational services in MTs Negeri 4 Cilacap, and to find out the constraints and challenges of marketing educational services in MTs Negeri 4 Cilacap. This type of research qualitative method is descriptive, the research subjects taken are the Head of Madrasah, Waka Public Relations, Waka Kesiswaan, Waka Curriculum, Operators, and Students. By conducting data collection techniques used by researchers using observation, interviews, and documentation. The result of this study is the application of a service marketing mix marketing strategy in MTs Negeri 4 Cilacap which emphasizes the 7P, namely product, price, place, promotion, people, physical evidence, and process. With this, it can be seen that madrasah in marketing its products in improving quality shows its excellence which can be seen from special programs, extracurricular activities, achievements achieved, better infrastructure, quite professional human resources, and an increase in the number of students every year. In carrying out the promotion of MTs Negeri 4 Cilacap, banners were installed, socialization to SD/MI, the use of social media such as Facebook, Youtube, Instagram and the use of websites. However, there are still educators and education personnel who need to be improved in awareness of the use of communication technology and facilities such as wifi in the sustainability of promoting madrasas.